The tetracyclic diterpenes - Hanson, James Ralph (International series of monographs in organic chemistry, 1968)
International Series of Monographs in Organic Chemistry, Volume 9: The Tetracyclic Diterpenes covers the physico-chemical properties, stereochemistry, reactions, and synthesis of various tetracyclic diterpene compounds. Each chapter of this eight-chapter book describes specific tetracyclic diterpene. The opening chapters focus on the members of the kaurene-phyllocladene class, which are best known and most widely distributed of the tetracyclic diterpenes. The subsequent chapters deal with other classes, including gibberellins, the stachene class, tetracyclic diterpenes alkanoids, and aconite.